Implementasi Business Intelligence dan Metode TOPSIS dalam Sistem Pendukung Keputusan Pemilihan Produk Terlaris pada Toko Retail Berbasis Dashboard Analitik - Nurul Mukharomi Azizah; Wargijono Utomo (JURNAL RISET MANAJEMEN (JURMA), 2026)
This research aims to implement Business Intelligence and the TOPSIS method in a Decision Support System for selecting the best-selling products in retail stores through an analytical Dashboard. Retail businesses generate large amounts of transaction data every day, but the data is often only used for operational reporting and has not been optimally utilized for strategic decision making. This study integrates Business Intelligence technology, data Warehouse, ETL process, Dashboard Analytics, and TOPSIS method to analyze product sales patterns and determine the best-selling products based on several criteria such as sales quantity, stock turnover, profit level, customer demand, and sales frequency. The research method uses a system development approach consisting of data collection, dimensional modeling, ETL implementation, TOPSIS calculation, Dashboard design, and system evaluation. The results show that the implemented system can accelerate reporting processes, improve decision-making accuracy, and assist management in identifying strategic products quickly and interactively. The integration of TOPSIS with Business Intelligence Dashboards contributes to effective data-driven decision making in retail management.